An analysis of focused metalinguistic written feedback: How would learners react? - Rizqiyyah, Rizqiyyah; Prianty, Tanty (Englisia Journal, 2020)
Learners of higher education are encouraged to write a scholarly publication in that it helps corroborate them as professionals in their fields of study. Practices in academic writing are thus indispensable to do to achieve a higher level of competency. This study explores learners’ reactions towards focused metalinguistic written feedbacks provided by a lecturer. The lecturer used electronic mail to provide constructive feedback to her students. This mixed-method study involved 22 post-graduate students from an Indonesian university. In analyzing the qualitative data, the researchers employed Miles and Huberman’s qualitative data analysis approach. Meanwhile, the quantitative data, namely the basic analysis of focused metalinguistic written feedbacks were analyzed by employing Cumming’s writing approach. The findings reveal that: (1) learners revised and expanded their draft after getting back their paper; (2) lecturer’s feedbacks through email have reportedly motivated learners because such the feedbacks did not lead learners perplexity compared to the handwritten feedbacks; (3) the majority of participants used revising and responding, consulting a dictionary/grammar book, and referring to the previous composition as the ways to handle lecturer’s input.